A Prospective Efonidipine Efficacy Evaluation in Cardiovascular and Renal Outcomes in Hypertensive Patients: The PERFECT Trial - Dewan, Bhupesh; Shinde, Siddheshwar; Kondekar, Shweta; Motwani, Nisha (British Journal of Healthcare and Medical Research, 2024)
Background: Efonidipine, an L and T-type calcium channel blocker (CCB), is known for effectively lowering blood pressure and targeting proteinuria by balancing glomerular capillary pressure. There remains a gap in understanding how its clinical benefits and safety profile compare to other CCBs, particularly those targeting L and N-type channels. The present trial evaluated the effect of Efonidipine and Cilnidipine on cardiovascular and renal outcomes in hypertensive patients. Methods: A randomized, comparative trial was conducted from May 2019 to August 2023 in adults with hypertension (≥140/90 mmHg). The patients (n=1035) received one of the drugs daily for 90 days. The primary endpoint was the change in blood pressure with secondary endpoints including improvement in proteinuria, and safety assessment. Results: Both Efonidipine and Cilnidipine reduced blood pressure to a similar extent (Efonidipine, from 155.17 ± 10.38 to 132.92 ± 9.60 mmHg, p<0.001; Cilnidipine, from 154.75 ± 10.05 to 132.90 ± 9.47 mmHg, p<0.001) and maintained heart rate significantly lower from baseline (Efonidipine, from 83.5 ± 7.2 to 80.1 ± 6.3 beats/ min, p<0.001; Cilnidipine, from 83.3 ± 6.9 to 80.0 ± 6.8 beats/min; p<0.001). Efonidipine demonstrated a more pronounced reduction (from 151.45 ± 4.4 to 123.52 ± 3.9 mg/g Cr, p<0.001) in proteinuria compared to Cilnidipine (from 161.64 ± 8.9 to 152.10 ± 3.9 7.8 mg/g Cr, p=4240). An independent decrease in proteinuria relative to blood pressure reduction was observed with Efonidipine. Adverse events were similar between groups, with no incidences of peripheral edema. Conclusion: Efonidipine and Cilnidipine effectively controlled blood pressure and reduced proteinuria. The antiproteinuric effect was more apparent with Efonidipine. Efonidipine improves cardiovascular and renal outcomes and may be considered an initial treatment option in hypertensive patients.